2004
DOI: 10.1590/s1413-86702004000200003
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis B and C in the Western Brazilian Amazon region (Rio Branco, Acre): a pilot study carried out during a hepatitis B vaccination program

Abstract: In 1999, on the occasion of the application of the first vaccine dose during the state vaccination campaign against hepatitis B virus (HBV), 390 individuals from the town of Rio Branco, Acre, aged two or more years were selected for the determination of the seroprevalence of HBV and HCV. HBV markers (HBsAg, anti-HBs, and anti-HBc IgG) were determined on this occasion and anti-HBs antibodies were also assessed 30 days after the third vaccine dose. At the time of vaccination, 39% of the individuals were still su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
7
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 14 publications
(12 reference statements)
3
7
0
2
Order By: Relevance
“…25,26,[35][36][37][38] The presence of HBsAg, the most commonly used marker to determine present infection, is an important tool for evaluating the mechanisms of transmission dynamics, its principal actors, and for identifying the population at potential risk of chronic liver disease. HBsAg = hepatitis B surface antigen; N = number of subjects; N+ = number of positive subjects; F = female; M = male; 95% CI = 95% confidence interval; *AOR = adjusted odds ratio for the following variables: age, village, past family history of clinical Malaria, vaccination against HBV, and presence of HBeAg-reactive in the Family; P value = statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…25,26,[35][36][37][38] The presence of HBsAg, the most commonly used marker to determine present infection, is an important tool for evaluating the mechanisms of transmission dynamics, its principal actors, and for identifying the population at potential risk of chronic liver disease. HBsAg = hepatitis B surface antigen; N = number of subjects; N+ = number of positive subjects; F = female; M = male; 95% CI = 95% confidence interval; *AOR = adjusted odds ratio for the following variables: age, village, past family history of clinical Malaria, vaccination against HBV, and presence of HBeAg-reactive in the Family; P value = statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the prevalence in the general population varies greatly from very low rates of 0.1% in the semi-arid Northeast Region (Focacia et al 1998, Tavares-Neto et al 2005, Figueiró-Filho et al 2007) to higher rates in the Amazon Region of 4-6% (Tavares- Neto et al 2004, Silva et al 2006, Paraná et al 2007). The HCV seroprevalence encountered in this study was similar to those found in some populations considered to be at risk for HCV infection, including 15% and 11% prevalence in alcoholics and chronic renal patients undergoing hemodialysis, respectively (Galperim et al 2006, Freitas et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…The nationwide epidemiological situation for HBV, HCV and HIV infections is difficult to quantify due to local and regional characteristics as well as the high number of asymptomatic infections (Tavares-Neto et al 2004, Silva et al 2006. Furthermore, most Brazilian studies, particularly ones dealing with hepatitis, were carried out in selected populations (e.g., prisoners, individuals with renal failure undergoing hemodialysis, intravenous injection drug users and health care workers) (Paraná et al 2007, Fialho et al 2008, Oliveira et al 2009).…”
mentioning
confidence: 99%
“…The prevalence of the HBsAg was estimated at less than 1% in the Northeast and CentralWest regions (Pereira et al 2009) and around 1% in the municipality of São Paulo (Focaccia et al 1998). In the Brazilian Amazon region, a higher prevalence was estimated to be 3.3-20.6% in some specific populations, such as certain indigenous groups (Braga et al 2001, 2005, Tavares-Neto et al 2004.…”
mentioning
confidence: 99%